Comparative Study of Human Rights Protection: An Analysis between Germany and Indonesia - Suharsono, Agus (Universitas Muhammadiyah Yogyakarta, 2024)
This study aims to compare the issue of human rights protection between Germany, which is among the top five rule of law indexes, and Indonesia, which is in the middle position. The research is normative legal research, relying primarily on secondary sources in the form of legal materials, particularly constitutions and statutes. The result of the study shows that Germany has a strong legal system and high public awareness of human rights, which contributes to the implementation of human rights protection more effectively than Indonesia. Germany has consistently shown improvements in fundamental rights, while Indonesia still faces challenges in the implementation of fair legal processes, legal oversight, and social norms that are still discriminatory. Although Indonesia has made democratic progress, there is still a need for legal system reform, harmonization of laws, and increased public awareness to improve human rights protection. Indonesia must strengthen and harmonize human rights laws, reform the judiciary for greater independence, and establish an independent authority for personal data protection. It is crucial to change discriminatory social norms, clarify religious freedom laws, address religious minority discrimination, improve labor supervision, and enhance the role of trade unions for better human rights protection.